22 Myocardial perfusion is influenced by age, gender, diabetes, myocardial fibrosis and the use of beta-blockers: a perfusion mapping study. (May 2018) - Knott, Kristopher D; Camaioni, Claudia; Bhuva, Anish N; Brown, Louise AE; Xue, Hui; Manisty, Charlotte H; Plein, Sven; Kellman, Peter; Moon, James C
Abstract : Introduction: Myocardial perfusion is determined by epicardial coronary flow and the microvasculature. It is now possible to quantify perfusion non-invasively using inline quantitative perfusion mapping. We investigated patients with chest pain but unobstructed epicardial coronary arteries to determine the factors that contribute to myocardial perfusion. Methods: Patients with unobstructed coronary arteries who had also undergone perfusion CMR were included. Myocardial blood flow (MBF) at stress and rest was measured on a per-segment basis and averaged to calculate a global flow. A univariate analysis and multiple linear regression analysis was performed to determine the factors influencing perfusion. Results: 110 patients with a mean age of 56.6 years, 50% male were studied. There was a high prevalence of cardiovascular risk factors – hypertension 50%, dyslipidaemia 37%, smoking history 32%, type 2 diabetes 16%. Mean stress MBF was 2.53 ml/g/min, rest MBF 0.91 ml/g/min and MPR 2.91. In a multiple linear regression analysis, increasing age (p<0.01), diabetes (p<0.01), LGE (p<0.05) and beta blocker therapy (p<0.01) was associated with reduced stress MBF. The overall R 2 for the model was 0.355. Rest MBF was increased in females (p<0.01) and those with higher resting heart rates (p<0.01). The R 2 for the model was 0.231. Conclusion: Stress MBF is influenced by age, diabetes, myocardial fibrosis and beta blocker therapy. Rest MBF is affected by gender and resting heart rate. These factors need to be taken into consideration when developing normal ranges and quantifying perfusion in clinical practice.